ORGANIZATION CULTURE IMPACT TO PERFORMENT HOTEL EMPLOYE (CASE STUDY : HOTEL LEGIAN RESORT –BALI) - I Wayan Pantiyasa; Michelle Michelle (Journal of Business on Hospitality and Tourism, 2016)
Organisational culture is a set of values or personality that is implemented by certain company or hotel as a form of identity of that hotel or company. The effect of organisational culture is profound, and correlates heavily towards employee performance by enhancing individual performance and increasing employee retention. This research is conducted to discover the effect of organisational culture towards employee performance in Padma Resort Legian. The hotel’s established core values points are used by measuring the effect of each core values towards employee performance. Whereas the core values that had been established is as follows; achievement, excellence, customer focus, honesty and integrity and people oriented. Quantitative and qualitative method is used as a tool to unravel the connection between organisational culture towards employee’s performance. Later on questioners that had been distributed to 119 respondents by using likert scale measurement. The data then is analysed by using both simple and multiple correlation to measure the corelation between the core values towards employees performance both entirely or partially. The result of the research shows that there is a correlation between organisational cultures towards employee’s performance entirely, although only achievement and customer focus that show a significant value of correlation towards employee’s performance.